Electron dynamics in transport and optical measurements of self‐assembled quantum dots. Issue 3 (4th January 2017) - Kurzmann, Annika; Merkel, Benjamin; Marquardt, Bastian; Beckel, Andreas; Ludwig, Arne; Wieck, Andreas D.; Lorke, Axel; Geller, Martin
Abstract: The tunneling dynamics between self‐assembled quantum dots (QDs) and a charge reservoir can be measured in an all‐electrical or optical detection scheme. In all‐electrical transconductance spectroscopy, a two‐dimensional electron gas is used to probe the evolution of the many‐particle states inside an ensemble of QDs from non‐equilibrium to equilibrium. The optical detection scheme measures the tunneling dynamic into a single self‐assembled dot. The work done and results obtained using these different measurement techniques are reviewed and compared within this article. We will show that transconductance spectroscopy is sensitive to a time‐dependent density of states and enables preparation of non‐equilibrium charge and spin states for future applications in quantum information processing. The optical resonance fluorescence measurements on the electron dynamics demonstrates the influence of the exciton states on the charge‐carrier dynamics and enables a systematic study of the Auger recombination in self‐assembled dots. Abstract : The electron tunneling between self‐assembled quantum dots (QDs) and a charge reservoir is observed in transport and optical measurements. The time‐resolved evolution of the density of states from non‐equilibrium to equilibrium is observed in transport spectroscopy. In time‐resolved resonance fluorescence on a single dot, the influence of the optical excitation on the tunneling events and the Auger recombination was studied.